2020
DOI: 10.1002/chem.202002779
|View full text |Cite
|
Sign up to set email alerts
|

Escaping from Flatland: Stereoconvergent Synthesis of Three‐Dimensional Scaffolds via Ruthenium(II)‐Catalyzed Noyori–Ikariya Transfer Hydrogenation

Abstract: Noyori-Ikariya-type ruthenium(II)-catalysts for asymmetric transfer hydrogenation(ATH) have been known for 25 years and have proved asawell-behaved and userfriendly platform for the synthesis of chiral secondary alcohols. Ap rogress has been made in the past five years in understanding the asymmetric reduction of complex ketones, where up to four stereocenters can be controlled in as ingle chemical transformation. Intriguing multi-chiral molecular architecturesa re therefore available in few well understood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 92 publications
(94 reference statements)
2
31
0
Order By: Relevance
“…Furthermore, we have also considered the possibility of conducting the kinetic resolution of 1a′ through asymmetric reduction such as transfer hydrogenation. 16 As demonstrated in Scheme 3c, using classical Noyori–Ikariya type catalysts D 17 a and E 17 b , we found that the hydrogenation afforded a new diastereoisomer trans - 1a , which is very different from the products obtained using NaBH 4 reduction; secondarily, all attempts to achieve efficient kinetic resolution using D or E failed, and very low ee values of trans - 1a or recovered 1a′ were detected (Scheme 3c). All these results clearly demonstrate that the KRA* method is currently irreplaceable.…”
mentioning
confidence: 80%
“…Furthermore, we have also considered the possibility of conducting the kinetic resolution of 1a′ through asymmetric reduction such as transfer hydrogenation. 16 As demonstrated in Scheme 3c, using classical Noyori–Ikariya type catalysts D 17 a and E 17 b , we found that the hydrogenation afforded a new diastereoisomer trans - 1a , which is very different from the products obtained using NaBH 4 reduction; secondarily, all attempts to achieve efficient kinetic resolution using D or E failed, and very low ee values of trans - 1a or recovered 1a′ were detected (Scheme 3c). All these results clearly demonstrate that the KRA* method is currently irreplaceable.…”
mentioning
confidence: 80%
“…Consequently, modifications on the arene ligands allow a fine tuning of the enantiomeric excess, which can be favoured by tethered ligands in which the arene is covalently bound to the diamine, increasing the stability and turnover of the catalyst. 40,41…”
Section: Asymmetric Transfer Hydrogenation (Ath)mentioning
confidence: 99%
“…Furthermore, asymmetric hydrogenation (AH) 27–34 and asymmetric transfer hydrogenation (ATH) 35–44 have arisen as potent methodologies for the preparation of chiral compounds. As a result, they have been extensively explored in the synthesis of a variety of natural scaffolds and pharmaceutics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetric transfer hydrogenation (ATH) has been reported by Lassaletta and co-workers [ 5 ] as a method to access enantiomerically enriched fluoro-tetralol via a dynamic kinetic resolution (DKR) process ( Scheme 1 a). Following the premise of the fluorine need and the previous works in the laboratory including the ATH/DKR of 3-fluoro-chromanone derivatives [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] ( Scheme 1 b), we herein report an asymmetric transfer hydrogenation/dynamic kinetic resolution [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] (ATH/DKR) of tert -butyl 3-fluoro-4-oxo-3,4-dihydroquinoline-1(2 H )-carboxylates into the corresponding enantioenriched cis -fluorohydrins ( Scheme 1 c).…”
Section: Introductionmentioning
confidence: 99%